2012
DOI: 10.1586/eri.12.87
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for potentiation of ethionamide and folate antagonists againstMycobacterium tuberculosis

Abstract: Antifolates inhibit de novo folate biosynthesis, whereas ethionamide targets the mycolate synthetic pathway in Mycobacterium tuberculosis. These antibiotics are effective against M. tuberculosis but their use has been hampered by concerns over toxicity and low therapeutic indexes. With the increasing spread of drug-resistant forms, interest in using old drugs for tuberculosis treatment has been renewed. Specific inhibitors targeting resistance mechanisms could sensitize M. tuberculosis to these available, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 82 publications
(201 reference statements)
1
23
0
Order By: Relevance
“…Yet, a parallel study reported that while sulfamethoxazole alone showed measurable activity against various M. tuberculosis isolates, no apparent improvement of trimethoprim activity was observed (70). Interestingly, it has been demonstrated that specific disruptions in the folate interconversion pathway can modulate the susceptibility of M. smegmatis to various trimethoprim-sulfonamide combinations (72), suggesting opportunities for potentiation of antifolate action in mycobacteria (73).…”
Section: Folate Metabolism As a High-value Drug Targetmentioning
confidence: 99%
“…Yet, a parallel study reported that while sulfamethoxazole alone showed measurable activity against various M. tuberculosis isolates, no apparent improvement of trimethoprim activity was observed (70). Interestingly, it has been demonstrated that specific disruptions in the folate interconversion pathway can modulate the susceptibility of M. smegmatis to various trimethoprim-sulfonamide combinations (72), suggesting opportunities for potentiation of antifolate action in mycobacteria (73).…”
Section: Folate Metabolism As a High-value Drug Targetmentioning
confidence: 99%
“…tuberculosis infections13. The search for new therapeutic options for treatment of drug susceptible as well as drug resistant strains has fueled an effort to repurpose existing drugs for TB therapy45.…”
mentioning
confidence: 99%
“…Two research groups recently reported the identification of ethionamide potentiators that significantly sensitize M. tuberculosis to the drug through the inactivation of a key resistance mechanism [36]. Hopefully, the introduction of effective potentiators would allow ethionamide to be used as a first-line anti-TB agent [36].…”
Section: Key Pointsmentioning
confidence: 99%